2022
DOI: 10.3390/nu14061265
|View full text |Cite
|
Sign up to set email alerts
|

Eating out of Home: Influence on Nutrition, Health, and Policies: A Scoping Review

Abstract: Eating out of home (EOH) is a common practice worldwide but research gaps have been identified. The aims of this review were (a) to find a common definition for EOH, (b) to determine the nutritional contribution of EOH, and (c) to analyze the relationship of EOH with health parameters in adults. Fifty-seven articles were finally selected. The definition of EOH was not harmonized between researchers and the comparison between studies was quite difficult. Restaurant and fast food were the terms most used, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 64 publications
(279 reference statements)
1
23
1
Order By: Relevance
“…First, as contemporary food industries and technologies have developed rapidly [ 72 ], people are beginning to prefer a wide range of processed food due to the affordable price and ready availability [ 27 , 73 ]. Moreover, as a result of the time-pressured social environment, people are becoming increasingly dependent on eating out and snacking, which involve a high calorie intake but only limited nutrition [ 74 , 75 , 76 ]. Irregular lifestyles characterized by insufficient sleep, excessive drinking, and/or high stress levels also disrupt the secretion of the hormones that control appetite and instigate compulsive overeating [ 77 ].…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…First, as contemporary food industries and technologies have developed rapidly [ 72 ], people are beginning to prefer a wide range of processed food due to the affordable price and ready availability [ 27 , 73 ]. Moreover, as a result of the time-pressured social environment, people are becoming increasingly dependent on eating out and snacking, which involve a high calorie intake but only limited nutrition [ 74 , 75 , 76 ]. Irregular lifestyles characterized by insufficient sleep, excessive drinking, and/or high stress levels also disrupt the secretion of the hormones that control appetite and instigate compulsive overeating [ 77 ].…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…Additionally, studies have confirmed that eating outside the home is occurring more frequently due to lifestyle changes, but the effect of this may vary depending on the country and eating out is not always necessarily unhealthy. In some countries, this may be an indicator of a higher socioeconomic status, while in other countries, this is a cheaper way of eating, usually marked by frequent fast food consumption and poor lifestyle habits [ 54 ]. For example, in our study, reading labels on food products showed a weak positive association with eating outside the home.…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency of eating out is also related to poorer diet quality. In general, individuals who consume food away from home present lower intakes of fiber, dairy, fruit, vegetables, and micronutrients than non-consumers [ 2 ]. Beyond individual health, away-from-home food has many other implications for the environment that should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017–2018, one-third of the expenditures on food were for away-from-home foods (AFHF) [ 1 ]. It is well-known that AFHF consumption has a substantial impact on daily caloric intake due to the high content of total fat and saturated fat in foods prepared away from home [ 2 ]; however, little attention has been given to the contribution of away-from-home food to environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%